The energy balance of the asymmetric combined inductive-capacitive RF discharge at low pressure - Zykov, A.V.; Polozhiy, K.I.; Farenik, V.I. (Вопросы атомной науки и техники, 2003)
The combined inductive-capacitive RF discharge at low gas pressure is considered for a case of collisionless ion motion. The power distribution model in the combined RF discharge in case of two asymmetric RF electrodes is developed in term of a ratio of the electrode areas and in term of a magnitude of applied RF voltage. We believe that power distributes on three parts: ionization and acceleration of ions in two electrode-sheath transitions. Two types of design is considered: with one and two RF generators. The dependencies of the dissipated RF power parts are obtained in terms of external discharge parameters. It is revealed an existence of a power maximum on acceleration of ions at electrode, which has a lower area. Been accorded expression for dependence of optimum discharge parameters. At using the power distribution model results the system parameter correlation’s have been obtained for a maximum process effectiveness of physical sputtering for systems on the basis of combined inductive-capacitive discharge.